1983
DOI: 10.1161/01.hyp.5.5.749
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of metoprolol on muscle sympathetic activity in hypertensive humans.

Abstract: Recordings of multiunit sympathetic activity were made from muscle branches of the peroneal nerve in eight previously untreated subjects with essential hypertension during intravenous administration of the cardioselective beta-adrenoceptor antagonist, metoprolol. Intraarterial blood pressure and central venous pressure were monitored simultaneously. After metoprolol, heart rate fell and central venous pressure increased in all subjects. Blood pressure increased in some subjects and decreased in others whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
2
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 22 publications
4
13
2
1
Order By: Relevance
“…Previous studies in humans have reported an increased MSNA after acute metoprolol 11 or propranolol 12 administration, in keeping with our findings. In regard to the mechanism that may account for the remarkable increase of MSNA observed in the present study after atenolol administration, the lack of changes in both arterial pressure values and in the ␣-index of cardiac baroreflex control seems to reasonably exclude a role played by arterial baroreceptor unloading.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies in humans have reported an increased MSNA after acute metoprolol 11 or propranolol 12 administration, in keeping with our findings. In regard to the mechanism that may account for the remarkable increase of MSNA observed in the present study after atenolol administration, the lack of changes in both arterial pressure values and in the ␣-index of cardiac baroreflex control seems to reasonably exclude a role played by arterial baroreceptor unloading.…”
Section: Discussionsupporting
confidence: 92%
“…Conflicting results have also been reported by studies using direct recordings of postganglionic sympathetic neural discharge (muscle sympathetic nerve activity [MSNA]), which was found to be increased 11,12 or unchanged 13 after acute ␤-blockade.…”
mentioning
confidence: 99%
“…Previous studies by Sundlöf et al 34 and Wallin et al 35 demonstrated that in patients with untreated essential hypertension, a marked acute reduction in arterial pressure resulted in an increase in MSNA during administration of a cardioselective ␤-adrenoceptor antagonist metoprolol or a low dose of a central sympathoinhibitory agent clonidine. Recently, Grassi et al 36 found that acute administration of an antihypertensive drug with peripheral vasodilator agent prazosin or a combination of central and peripheral modes of action urapidil activated the sympathetic nervous system to a similar extent in untreated hypertensive patients, and they thereby concluded that adrenergic activation was generalized to any drug-induced acute BP fall, presumably because of a lack of a sympathetic baroreflex resetting during acute antihypertensive treatment.…”
Section: Hyzaar and Absence Of Sympathetic Baroreflex Resettingmentioning
confidence: 99%
“…In this regard, it is of interest that at higher doses of propranolol diastolic blood pressure falls more rapidly, and more closely follows the time-course of the decrease in systolic blood pressure (Maling et al, 1979;Serlin et al, 1983). A decrease in cardiac output, as caused by propranolol at both lower and higher dose levels, is thought to elicit a compensatory rise in total peripheral resistance via baroreflexes and increased peripheral sympathetic tone (Morganti et al, 1979;Sundlof et al, 1983), and thus maintaining diastolic blood pressure. Resetting of the baroreceptors will then gradually occur, resulting in a delayed fall in diastolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%